Psychiatric and neurodevelopmental disorders in childhood-onset epilepsy - Berg, Anne T.; Caplan, Rochelle; Hesdorffer, Dale C. (Epilepsy & behavior, 2011)
Childhood-onset epilepsy is associated with psychiatric and cognitive difficulties and with poor social outcomes in adulthood. In a prospective cohort of young people with epilepsy, we studied psychiatric and neurodevelopmental disorders and epilepsy-related characteristics, all factors that may influence long-term social outcomes. Five hundred one subjects, 159 with complicated (IQ <80 or brain lesion) and 342 with uncomplicated epilepsy, were included. Psychiatric disorders and neurodevelopmental disorders were more common in complicated epilepsy (P<0.005). In uncomplicated epilepsy, externalizing but not internalizing disorders were strongly associated with neurodevelopmental disorders. Internalizing disorders and neurodevelopmental disorders were associated with lack of 5-year remission. Type of epilepsy was not associated with neurodevelopmental disorders or psychiatric disorders. Various comorbid conditions in epilepsy cluster together and are modestly associated with imperfect seizure control. These need to be considered together in evaluating and managing young people with epilepsy and may help explain long-term social outcomes above and beyond poor seizure control. ► Neurodevelopmental and psychiatric disorders are common in childhood-onset epilepsy. ► They are strongly correlated, especially in children of normal intelligence. ► There may be long-term effects of these beyond the impact of seizures themselves.